Fatal varicella in immigrants from tropical countries: Case reports and forensic perspectives. (May 2018) - Guadagnini, Gianni; Lo Baido, Simone; Poli, Francesca; Govi, Annamaria; Borin, Sveva; Fais, Paolo; Pelotti, Susi
Highlights: Primary VZV infection is typically acquired during adulthood in the tropics. Adults emigrating from the tropics are susceptible to severe varicella. Varicella in adults emigrating from the tropics display poorer outcomes. Death may occur despite proper management. Vaccination strategies are advisable for adult immigrants from the tropics. Abstract: The primary Varicella Zoster Virus (VZV) infection results in varicella, a generally benign, self-limiting disease in immunocompetent children. Despite the usual course a possible fatal evolution of the primary infection is observed predominantly in immunocompromised subjects and in adults, especially emigrating from tropical regions. Two cases of fatal varicella have been investigated and discussed. Death occurred in two patients over 40 years of age, coming from South Asia and receiving chronic immunosuppressive therapy. The forensic expert must be cautious and consider all clinical records in managing fatal varicella cases, bearing in mind risk factors and pre-existing conditions such as age, geographical provenance and pathological comorbidity, which may lead to a bad prognosis irrespective of therapies. Based on the severe and fatal course observed in the reported cases, an extension of the immunization program appears advisable for immigrants from tropical countries, especially before scheduled immunotherapy.